2010
DOI: 10.1093/gerona/gls078
|View full text |Cite
|
Sign up to set email alerts
|

The Safety, Pharmacokinetics, and Effects of LGD-4033, a Novel Nonsteroidal Oral, Selective Androgen Receptor Modulator, in Healthy Young Men

Abstract: LGD-4033 was safe, had favorable pharmacokinetic profile, and increased lean body mass even during this short period without change in prostate-specific antigen. Longer randomized trials should evaluate its efficacy in improving physical function and health outcomes in select populations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
121
1
12

Year Published

2014
2014
2021
2021

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 127 publications
(138 citation statements)
references
References 39 publications
4
121
1
12
Order By: Relevance
“…Virilisation was not noted in any of the patients (96) . A novel class of drugs, selective androgen receptor modulators, has recently received tremendous research endeavour for their ability to increase muscle mass in clinical studies; however, their effects on musle strength or exercise capacity are not yet convincing (97)(98)(99)(100)(101) . Studies in HF are not available.…”
Section: Treatment Approaches To Wasting In Heart Failurementioning
confidence: 99%
“…Virilisation was not noted in any of the patients (96) . A novel class of drugs, selective androgen receptor modulators, has recently received tremendous research endeavour for their ability to increase muscle mass in clinical studies; however, their effects on musle strength or exercise capacity are not yet convincing (97)(98)(99)(100)(101) . Studies in HF are not available.…”
Section: Treatment Approaches To Wasting In Heart Failurementioning
confidence: 99%
“…Clinical studies of these SARMs are focused on the correction of sarcopenia in elderly, patients with chronic diseases and cancer cachexia [140,141] and not for androgen replacement therapy. Use of these agents for treatment of hypogonadism is not a priority for development for many of these new agents.…”
Section: Options For Testosterone Replacement Therapymentioning
confidence: 99%
“…The phase I trial showed an increase in muscle mass in a short period, with no effect on fat mass. 65) Enobosarm (GTx-024) is an orally bioavailable non-steroidal SARM. The use of enobosarm led to significant improvements in lean body mass and physical function in a phase II, double-blind, placebo-controlled studies both in healthy elderly adults and in cancer patients.…”
Section: )mentioning
confidence: 99%